2010
DOI: 10.1089/jir.2009.0033
|View full text |Cite
|
Sign up to set email alerts
|

Gram-Positive and Gram-Negative Bacteria Induce Different Patterns of Cytokine Production in Human Mononuclear Cells Irrespective of Taxonomic Relatedness

Abstract: Upon bacterial stimulation, tissue macrophages produce a variety of cytokines that orchestrate the immune response that clears the infection. We have shown that Gram-positives induce higher levels of interleukin-12 (IL-12), interferon-gamma (IFN-gamma), and tumor necrosis factor (TNF) from human peripheral blood mononuclear cells (PBMCs) than do Gram-negatives, which instead induce more of IL-6, IL-8, and IL-10. Here, we study whether these patterns follows or crosses taxonomic borders. PBMCs from blood donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 29 publications
5
43
0
Order By: Relevance
“…In our study, both intact Gram-positive bacteria and LTA components were found to be the more effective adjuvants for DC vaccination in a therapeutic setting compared with other TLR agonists. The enhanced adjuvant effect of Gram-positive preparations in our study and that of others (55,56) may reflect the superior induction of inflammatory cytokines by Gram-positive bacteria, without the induction of IL-10 observed with Gram-negative bacteria (33,57).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In our study, both intact Gram-positive bacteria and LTA components were found to be the more effective adjuvants for DC vaccination in a therapeutic setting compared with other TLR agonists. The enhanced adjuvant effect of Gram-positive preparations in our study and that of others (55,56) may reflect the superior induction of inflammatory cytokines by Gram-positive bacteria, without the induction of IL-10 observed with Gram-negative bacteria (33,57).…”
Section: Discussionsupporting
confidence: 53%
“…Superior induction of IFN-g from splenocyte cocultures was achieved with Gram-positive preparations, and the activity was shown to be dependent on NK cells (34). The particular strain of S. salivarius selected to enhance DC activation for tumor immunotherapy has the additional advantage of a lack of mammalian toxin sequences, a demonstrated lack of pathogenicity, and is widely used in humans as an oral probiotic (52), yet is a potent inducer of IL-12 and IFN-g in human and murine leukocytes (33,34). Although bacteria induce potent activation of DC enabling optimal T cell stimulation (53, 54), we cannot rule out that host responses to bacterial products associated with S. salivarius-matured DC may also contribute to the potency of the observed immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that procalcitonin, but not CRP and WBC counts, is associated with gram-negative bacteria (28). Due to the different components of the cell (29,30). Therefore, we hypothesized that inflammatory molecules in the serum may provide information for identifying bacterial species.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, we hypothesized that inflammatory molecules in the serum may provide information for identifying bacterial species. Gram-negative bacteria induce higher levels of IL-6, IL-10 and IL-8 compared with gram-positive bacteria in human monocytes (29)(30)(31). To the best of our knowledge, there are few studies reporting whether cytokines or chemokines could be markers to distinguish infection of gram-positive or gram-negative bacteria in patient serum.…”
Section: Discussionmentioning
confidence: 99%